المعرفة المحاسبية: الاصل والتوجه الجديد في ادارتها - د. صالح ابراهيم يونس الشعباني (PROSPECTIVE RESEARCHES, 2023)
Knowledge of accountancy is an applied art developed then to be an approved and believable science. It deals with harmony and persuasion in presenting the accounting information. Knowledge of accountancy had various stages since the time during which it was written in clay tablets and candles as a means of remembering. As a result, it has become an electronic information system. This change in stages is the result of the economic and social development as well as the use of accounting information in industrial commercial, service and banking field. There was a need for information science, This is due to the use of modern industrialization system as CIM ,the effect of the conditions of excellence, the desire of low cost and the use of operation researches in accounting applications and analytical techniques like the value series. This is supported by the use of the computer where most if not all procedures and accounting analyses are implemented electronically and the result is the display of huge amount of information which is used ,for exampal , in decision making with the least effort ,This information is presented in suitable time ,specified place ,with the amount required and for every one who is in need by means of the internet . Knowledge of accountancy followed various approaches in the scientific research through its historical development mentioned above. Therefore, it was developed by the development of the concepts, the mathematical, statistical, economic and technological theories.